A High‐Performance D–A Copolymer Based on Dithieno[3, 2‐b:2′, 3′‐d]Pyridin‐5(4H)‐One Unit Compatible with Fullerene and Nonfullerene Acceptors in Solar Cells. Issue 14 (3rd April 2017) - An, Mingwei; Xie, Fangyuan; Geng, Xinjian; Zhang, Jianqi; Jiang, Jiaxing; Lei, Zhongli; He, Dan; Xiao, Zuo; Ding, Liming
Abstract : Development of high‐performance donor–acceptor (D–A) copolymers is vital in the research of polymer solar cells (PSCs). In this work, a low‐bandgap D–A copolymer based on dithieno[3, 2‐b:2′, 3′‐d]pyridin‐5(4H)‐one unit (DTP), PDTP4TFBT, is developed and used as the donor material for PSCs with PC71 BM or ITIC as the acceptor. PDTP4TFBT:PC71 BM and PDTP4TFBT:ITIC solar cells give power conversion efficiencies (PCEs) up to 8.75% and 7.58%, respectively. 1, 8‐Diiodooctane affects film morphology and device performance for fullerene and nonfullerene solar cells. It inhibits the active materials from forming large domains and improves PCE for PDTP4TFBT:PC71 BM cells, while it promotes the aggregation and deteriorates performance for PDTP4TFBT:ITIC cells. The ternary‐blend cells based on PDTP4TFBT:PC71 BM:ITIC (1:1.2:0.3) give a decent PCE of 9.20%. Abstract : A low‐bandgap D–A copolymer based on dithieno[3, 2‐b:2′, 3′‐d]pyridin‐5(4H)‐one unit, PDTP4TFBT, is developed and used as the donor material for polymer solar cells. PDTP4TFBT is among a few D–A copolymers that can deliver >7% power conversion efficiencies (PCEs) in both fullerene and nonfullerene solar cells. Ternary‐blend solar cells based on PDTP4TFBT, PC71 BM, and ITIC give a PCE of 9.20%.